The Potential of Singkawang City People From Aspect Of Harmony - Azeharie, Suzy; Sari, Wulan Purnama; Irena, Lydia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
As a multicultural country, the opportunities for clashes and conflicts in Indonesia are wide open. This is due to the plurality and heterogeneity of Indonesian society which is reflected in the form of cultural diversity, religion, lifestyle in society which is quite complex. In the history of West Kalimantan Province, various horizontal conflicts have alternated, including 1997 and 1999, the Madura conflict with Malay/Dayak etc. The number of fatalities and material losses is incalculable. Singkawang is one of the 12 Level II Regions and 2 Cities in West Kalimantan Province. This city was included as the most tolerant city in Indonesia in two selections by the SETARA Institute. There were hardly any outbreaks of escalating conflict, even though the city is predominantly inhabited by ethnic Malays and Chinese from the Hakka or Khek sub-ethnic. This qualitative research with case study method was conducted with the aim of knowing and describing the potential of the people of Singkawang City from the aspect of harmony. The research was conducted by collecting data through interviews with three resource persons living in Singkawang and Pontianak, namely with researchers from the Institute of Dayakology, Malay ethnic leaders and Dayak ethnic leaders. Another data collection technique was to collect data from research sources, internet journals and from various books. The conclusion of this study is that there are several supporting factors that make the Singkawang people live in harmony. Namely, among others, regional leaders who are considered to represent ethnic groups in Singkawang City. Then the people feel that the city government treats them fairly. This political recognition can be seen from the celebration of religious holidays of each religion which is carried out lively. However, the period leading up to and after the Pilkada is one of the factors to watch out for that can trigger conflict. This is due to the unique composition of the population of Singkawang city, namely the majority are citizens of Chinese descent, while the contestants put forward identity politics.